Factors Influencing Adoption of Tissue Culture Banana (TCB) Technology Among Banana Farmers in Chitwan District, Nepal - Singh, O.P. (NPI Journal of Science and Technology, 2024)
The adoption of tissue culture banana (TCB) technology promotes resistance to diseases, increased competitiveness, and a commitment to sustainability in the banana subsector. An investigation was carried out during 2021 to identify the factors influencing the adoption of TCB technology among banana farmers in Chitwan district, Nepal. Randomly 65 farm household were selected to gather primary data using semi structured questionnaire, further Focus Group Discussion (FGD) and Key Informant Interview (KII) was carried with selected individuals. Descriptive statistics and probit model was used to present the findings. Result revealed that adoption of TCB technology is significantly affected by annual farm household income, access to subsidy and access to credit. Hence, extension agencies of government and non-governmental institutions should primarily focus on farm household having higher income and access to credit for better adoption. A comprehensive policy approach considering market dynamics and infrastructure development is essential while delivering subsidy.